Pteridophytic Diversity of Sanjay National Park (Sidhi), Madhya Pradesh - Singh, Shweta; Dixit, R. D.; Sahu, T. R. (Indian Forester, 2005)
Pteridophytes form the dominant part of ground vegetation during rainy season. Total number of 14 families, 19 genera and 30 species of pteridophytes have been reported on the basis of published literature, herbarium consultation (BSA) and collections made by the author (Shweta Singh) from the area under report. The dominant families are Thelypteridaceae (6 Species) and Polypodiaceae (3 Species) respectively. Sanjay National Park consists of dense moist deciduous Sal forest. Madhuca and Diospyros species are also abundantly found in the Park. Dryopteris cochleata (Buch.-Ham. ex D. Don) C. Chr. occurs as common fern in the park. The species of Adiantum L., Selaginella P. Beauv., Tectaria Cav., and Dryopteris Adanson are medicinally used by local people in the area.